2019 29th Australasian Universities Power Engineering Conference (AUPEC) 2019
DOI: 10.1109/aupec48547.2019.211850
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Response of Synchronous Generators and Battery Energy Storage Systems: A Comparative Study

Abstract: In this paper, a comparison of power system frequency response is conducted for a simple modelled power system with primary frequency control being provided either by synchronous generators or by inverter-based Battery Energy Storage (BES) systems. Mathematical models of conventional governor and turbine are developed, representing conventional synchronous generator frequency control, and are used to illustrate system frequency response for a range of typical conventional generating units. A mathematical model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Several studies in the literature have proven the effectiveness of BESSs in providing this service. Amin et al [38] compared the provision of FCR by synchronous generators and a BESS using mathematical equations of governors and turbines. The results obtained showed that BESSs can provide a faster and better response to frequency deviations than synchronous generators.…”
Section: Services Provided By Besss and Revenue Stackingmentioning
confidence: 99%
“…Several studies in the literature have proven the effectiveness of BESSs in providing this service. Amin et al [38] compared the provision of FCR by synchronous generators and a BESS using mathematical equations of governors and turbines. The results obtained showed that BESSs can provide a faster and better response to frequency deviations than synchronous generators.…”
Section: Services Provided By Besss and Revenue Stackingmentioning
confidence: 99%
“…If the active power generation is higher than the load demand, the frequency increases above the nominal value and vice versa [14]- [16]. Increasing VG penetration in power grids while replacing conventional SGs increases the dynamic aspect of the power system due to decreased levels of system rotational inertia [17], [18]. In the event the generation side is lower than the net demand, the frequency evolves as shown in Figure 1.…”
Section: Preliminaries Of Power System Frequency Regulation 21 Conven...mentioning
confidence: 99%
“…In this study, we used our power system model to investigate the PFC response from SGs and RE NSGS in the QLD power system after the separation event and under a range of future scenarios. For this purpose, simplified mathematical models of a conventional governor and turbine were used, representing conventional synchronous generator frequency control, and described by Amin et al [11]. The inertia is defined as stored kinetic energy in watt-second ( 1 2 J ω 2 ); in the QLD power system it was 26,800 MWs at the time of separation [24].…”
Section: Lumped System Model and Separation Event Validationmentioning
confidence: 99%
“…A droop-type, lead-lag controlled BESSs is proposed by Datta et al [6] to provide additional damping of the system with around 18% PV penetration while satisfying the NEM regulatory requirements. Amin et al [11] presented a comparison of power system frequency response is presented for a simplified power system with primary frequency control (PFC) being provided by either synchronous generators or BESS. Amin et al [11] demonstrated that BESS enabled for PFC is capable of eliminating frequency undershoot and reducing settling time by 70%, after a major contingency event in a power system containing various types of conventional generation technologies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation